Sjeldne fugler i Norge i 2004 - Rapport fra Norsk sjeldenhetskomité for fugl (NSKF) - Mjølsnes, Kjell Ruud; Bunes, Vegard; Olsen, Tor Audun; Solbakken, Kjetil Aa. (Ornis Norvegica, 2006)
This is the 29th annual report and the 30th announcement from the Norwegian Rarities Committee (NSKF). The majority of records treated here are from 2004, but some older records are also included. Norway follows taxonomic advises given by the Taxonomic Advisory Committee (TAC) in the Association of European Rarity Committees (AERC). The systematic list of accepted records is set out in the following system: (1) The birds Norwegian name, (2) scientific name, (3) the numbers in brackets, e.g. (30/32 - 1), refers respectively to the total number of records/total number of individuals up to and including 2003, and in 2004, (4) any limitations given of (3), (5) any breeding, (6) year, (7) county, (8) number of individuals, age (1K = first calendar year etc.), sex (if known) and sometimes circumstances («rm» means that the bird was ringed), (9) site and municipality, (10) date, (11) * indicates if the record was complemented by positive evidence, and type of the evidence (F = photo, V = video-recorded, L = tape-recorded, D = found dead), (12) observers names in brackets, main observer is specified first and emphasized with *, (13) roughly gives the species distribution and (14) comments concerning the records. General trends: 2004 was one of the best years in the history of NSKF, With 223 accepted records. 76 accepted records from previous years help to complete the Norwegian Bird list. There are 22 records presented that have been shelved. Half of these are concerning first year «Eastern Yellow Wagtails». This is due to the lack of identification knowledge in the literature for such birds. Also presented are 47 records that for some reason have not been accepted. The records from 2004 shows few extraordinary trends, maybe except for a smaller influx of Sabine’s Gulls (16 records). It was the second best year for Green-winged Teal Anas carolinensis (10 records) and the best year for Bee-eater Merops apiaster (7 records) and Caspian Gull Larus cachinnans (4 records). Other records of interest are Norway’s fourth Short-toed Eagle Circaetus gallicus, sixth Gull-billed Tern Sterna niloctia, fifth Pallid Swift Apus pallidus, second White-winged Lark Melanocorypha leucoptera and second Eastern Bonelli’s Warbler Phylloscopus orientalis. Five records of White-winged Black Tern Chlidonias leucopterus and two records of Whites Thrush Zootera dauma are also more than normal. New species to the Norwegian list: There are a total of five new species to the Norwegian category A list presented in this report, all from 2004. This brings the official Norwegian Bird list to 471 species. Included in this list are accepted records in category A-C. The new species are Baird’s Sandpiper Calidris bairdii, Bridled Tern Sterna anaetheus, Thick-billed Warbler Acrocephalus aedon, Eastern Olivaceous Warbler Hippolais pallida and Eastern Orphean Warbler Sylvia crassirostris.